Enantioselective Vicinal Diacetoxylation of Alkenes under Chiral Iodine(III) Catalysis - Wöste, Thorsten H.; Muñiz, Kilian (Synthesis, 2016)
A procedure for the intermolecular enantioselective dioxygenation of alkenes under iodine(III) catalysis has been developed. This protocol employs Selectfluor as the terminal oxidant together with a defined C2-symmetric aryl iodide as the organocatalyst. This enantioselective reaction proceeds under mild conditions and converts a series of terminal and internal styrenes into the corresponding vicinal diacetoxylation products with up to 96% ee.
Keywords: alkenes; chirality; diacetoxylation; hypervalent iodine; oxidation; Selectfluor